2023
DOI: 10.1029/2022sw003231
|View full text |Cite
|
Sign up to set email alerts
|

Global Ionospheric TEC Forecasting for Geomagnetic Storm Time Using a Deep Learning‐Based Multi‐Model Ensemble Method

Abstract: High-reliable ionospheric prediction information is of great significance for precise positioning and navigation, space weather monitoring, as well as wireless communication (Schunk & Sojka, 1996;Zhang et al., 2022). Many models have been proposed to model the ionosphere and predict its changes. However, the prediction accuracy is limited due to the irregular characteristics and the complicated mechanism of ionospheric variations (Liu et al., 2022;Mcgranaghan et al., 2018). In recent years, the rapidly develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The data used in this paper, including the GIM-TEC, F10.7, ap, Kp, and Dst, as well as the program for the model, are available at Ren (2024).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…The data used in this paper, including the GIM-TEC, F10.7, ap, Kp, and Dst, as well as the program for the model, are available at Ren (2024).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Training the model with imbalanced EIC data, the mean square error (MSE) and a focal loss (L4) are utilized as loss functions to be minimized, for comparatively studying the improvement of the imbalanced regression by different loss functions. Many other machine learning models dealt with the imbalance problem by manually selecting only extreme events to improve the performance, for example, (Hu et al., 2023; Ren et al., 2023). We avoid providing such a priori knowledge to the predictive model, such that our model is robust to provide continuous predictions/forecasts in the real operational environment.…”
Section: Model Descriptionmentioning
confidence: 99%
“…They utilized seven different features to model 170 geomagnetic storm events. The results of their study showed that the DLMEM model was able to reduce the RMSE by an average of 43.6% compared to their previously presented model, Ion-LSTM [29]. LSTM is a powerful tool for handling temporal variations due to its memory retention capabilities, but it has limitations when dealing with problems that have both temporal and spatial characteristics.…”
Section: Introductionmentioning
confidence: 99%